DEVELOPMENT AND VALIDATION OF STABILITY INDICATING RP-HPLC METHOD FOR DETERMINATION OF β-ACETYLDIGOXIN - Sharma, Megha; Mahindroo, Neeraj (International Journal of Applied Pharmaceutics, 2016)
Objective: The objective of the present study was to develop and validate a novel stability indicating reverse phase-high performance liquid chromatography (RP-HPLC) method for determination of β-acetyldigoxin, an active pharmaceutical ingredient (API). Methods: The chromatographic separation was carried out on Agilent Technologies 1200 series HPLC system equipped with photo diode array detector and C-18 (4.6x250 mm, 5 µ) column. The mobile phase consisted of water: acetonitrile (65:35 v/v), delivered at a flow rate of 1.5 ml/min and eluents were monitored at 225 nm. Results: The retention time of β-acetyldigoxin was 9.2 min. The method was found to be linear (R2= 0.9995) in the range of 31.25-500 µg/ml. The accuracy studies showed the mean percent recovery of 101.02%. LOD and LOQ were observed to be 0.289 µg/ml and 0.965 µg/ml, respectively. The method was found to be robust and system suitability testing was also performed. Forced degradation analysis was carried out under acidic, alkaline, oxidative and photolytic stress conditions. Significant degradation was observed under tested conditions, except for oxidative condition. The method was able to separate all the degradation products within runtime of 20 min and was able to determine β-acetyldigoxin unequivocally in presence of degradation products. Conclusion: The novel, economic, rapid and simple method for analysis of β-acetyldigoxin is reported. The developed method is suitable for routine quality control and its determination as API, and in pharmaceutical formulations and stability study samples.